Lexical Cohesive Devices in Arab Students' Academic Writing: Implications for Teaching Vocabulary - El-Gazzar, Nevine Kamal (2006)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Nevine Kamal El-Gazzar Entitled, "Lexical Cohesive Devices in Arab Students' Academic Writing: Implications for Teaching Vocabulary," May 2006. Thesis Advisor is Dr. Fatima Badry. Available are both Soft and Hard Copies of the Thesis.